Microstructural evolution of a nickel-based superalloy during hot deformation. (15th July 2015) - Chen, Xiao-Min; Lin, Y.C.; Chen, Ming-Song; Li, Hong-Bin; Wen, Dong-Xu; Zhang, Jin-Long; He, Min
Graphical abstract: Highlights: Deformation parameters have significant influences on the grain microstructure. The dislocation substructure is also very sensitive to the deformation parameters. The bulging of initial grain boundaries is the main nucleation mechanism of DRX. The complete DRX domains are determined by DRX volume fractions contour map. Abstract: Hot compressive tests of a nickel-based superalloy are performed under the strain rate range of 0.001–1 s − 1 and deformation temperature range of 920–1040 °C. Optical microscopy (OM) and transmission electron microscopy (TEM) are employed to investigate the evolution of dynamic recrystallized (DRX) grain and dislocation substructure. It is found that the effects of deformation degree, strain rate and deformation temperature on DRX grain are significant. When the deformation degree or temperature is increased, the number of DRX grains rapidly increases. But, the increase of strain rate reduces the number of DRX grains. The dislocation substructure is also very sensitive to the deformation degree, strain rate and deformation temperature. With the increase of deformation degree, the evolution of dislocation substructure can be characterized as: high dislocation density → dislocation network → subgrain → DRX grain. Under high deformation temperatures or low strain rates, the dislocation substructure can be easily annihilated and rearranged because of the occurrence of DRX. Based on the evaluated DRX volume fractions, the contour map is constructed to optimize the hot deformation parameters.